A arquitetura do capital: expressão dialética do direito na Crítica da Economia Política de Karl Marx - Ana Clara Passos Presciliano (2021)
The work seeks to analyze the dialectical or dual character of law in Book I of Karl Marx's Capital, in order to demonstrate that it can at the same time reproduce the logic of capital, but also confront such logic. For this, in the first chapter, the fundamental assumptions of Karl Marx's Critique of Political Economy will be presented, brushing the aspects present in Books I, II and III of Capital that were considered relevant for the development of the other issues analyzed, and then move on in the second and third chapters by the passages of Book I of Capital dealing with law. In the meantime, works by authors of the so-called Marxist tradition, both national and foreign, in which the discussion promoted is present, will be addressed. Leaning on them and also on the passages of Book I of O Capital, it will be possible to present in chapter four what is defended as the dual character of law, but not without first conceptualizing the notion of dialectic in the Marxian work, telling more once with the help of the writings of Marxist authors on the subject. After this journey, the hypothesis that K. Marx's treatment of law is more tense and permeated by intricacies than what is normally assumed by the Marxist tradition will be demonstrated, moving away from unilateral readings and those that attribute a centrality to law within the mode of production. capitalist. Finally, it will be highlighted the one that rejects the law and its relevance in the analysis of social phenomena and delimits its role to a mere instrument of capital to achieve its purposes, or else reduce the scope of its study to the need to its overcoming, placing the end of capitalist society as a requirement for any social advance, does nothing (or very little) contribute so much to the debate on the subject as to the present situation of workers. This is because the daily demands and the need for subsistence are current and urgent, and they cannot wait to overcome the capitalist mode of production, which in no way means that the law itself is sufficient to meet these demands, nor that the struggle for the transformation of society would be of lesser importance, quite the opposite. Since the introduction of the text, there is a warning that its objective is not to overestimate the function of law, aware of Marx's statement that revolutions are not made through laws, nor that the revolutionary struggle should be left aside in for the struggles for rights. The caveat is that the struggles for rights do not exclude the revolutionary struggle, but only aim to ensure that this process takes place maintaining a decent standard of living conditions for its participants and affected.